(untitled) (Research, Society and Development, 2020)
Objective: To analyze the literature about the importance of the dental surgeon in the Intensive Care Units (ICU). Methods: This is an integrative literature review in which the search for data was performed on the Scientific Electronic Library Online (SciELO) and National Library of Medicine (PubMed) databases. Results: After analyzing the three articles included in the review, the results of the studies pointed to the existence of an interrelation between oral diseases and systemic conditions, directly compromising the integral health of individuals. Conclusion: It is essential that there is a consensus on the importance and need for dental work in the ICU environment, from the routine performance of patients’ oral hygiene to the implementation of more invasive procedures.